Microfluidic Antibody Affinity Profiling Reveals the Role of Memory Reactivation and Cross-Reactivity in the Defense Against SARS-CoV-2. - Denninger, Viola; Xu, Catherine K; Meisl, Georg; Morgunov, Alexey S; Fiedler, Sebastian; Ilsley, Alison; Emmenegger, Marc; Malik, Anisa Y; Piziorska, Monika A; Schneider, Matthias M; Devenish, Sean RA; Kosmoliaptsis, Vasilis; et al. (American Chemical Society (ACS), 2022)
Recent efforts in understanding the course and severity of SARS-CoV-2 infections have highlighted both potentially beneficial and detrimental effects of cross-reactive antibodies derived from memory immunity. Specifically, due to a significant degree of sequence similarity between SARS-CoV-2 and other members of the coronavirus family, memory B-cells that emerged from previous infections with endemic human coronaviruses (HCoVs) could be reactivated upon encountering the newly emerged SARS-CoV-2, thus prompting the production of cross-reactive antibodies. Determining the affinity and concentration of these potentially cross-reactive antibodies to the new SARS-CoV-2 antigens is therefore particularly important when assessing both existing immunity against common HCoVs and adverse effects like antibody-dependent enhancement (ADE) in COVID-19. However, these two fundamental parameters cannot easily be disentangled by surface-based assays like enzyme-linked immunosorbent assays (ELISAs), which are routinely used to assess cross-reactivity. Here, we have used microfluidic antibody affinity profiling (MAAP) to quantitatively evaluate the humoral immune response in COVID-19 convalescent patients by determining both antibody affinity and concentration against spike antigens of SARS-CoV-2 directly in nine convalescent COVID-19 patient and three pre-pandemic sera that were seropositive for common HCoVs. All 12 sera contained low concentrations of high-affinity antibodies against spike antigens of HCoV-NL63 and HCoV-HKU1, indicative of past exposure to these pathogens, while the affinity against the SARS-CoV-2 spike protein was lower. These results suggest that cross-reactivity as a consequence of memory reactivation upon an acute SARS-CoV-2 infection may not be a significant factor in generating immunity against SARS-CoV-2.
Funder: Universit?tsspital Z?rich
Funder: Biotechnology and Biological Sciences Research Council
Funder: NOMIS Stiftung
Funder: Universit?t Z?rich
Keywords: SARS-CoV-2; antibody affinity; antibody concentration; antibody profiling; cross-reactivity; microfluidics; Antibodies, Viral; Antibody Affinity; COVID-19; Humans; Microfluidics; SARS-CoV-2; Spike Glycoprotein, Coronavirus